2020
DOI: 10.1088/1361-6528/ab80fa
|View full text |Cite
|
Sign up to set email alerts
|

Structural effects of silver-nanoprism-decorated Si nanowires on surface-enhanced Raman scattering

Abstract: Surface enhanced Raman scattering (SERS) is an important analytical tool for the optochemical detection of molecules. The enhancement is commonly achieved by engineering (i) novel types and morphologies of plasmonic nanomaterials, and (ii) patterned or roughened supporting substrates of high surface area for increased light scattering and molecule adsorption. Si substrates can be easily and reproducibly textured for effective SERS applications. In this work, silver nanoprisms (AgNPr) coated silicon nanowire (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Finally, the SiNWs grown on the Si wafers were washed and dried at ambient atmosphere. The formation of the SiNWs array was prominently evident from the visual observation of black color over the substrate at the end of the preparation process [ 12 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the SiNWs grown on the Si wafers were washed and dried at ambient atmosphere. The formation of the SiNWs array was prominently evident from the visual observation of black color over the substrate at the end of the preparation process [ 12 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among several sophisticated analytical instruments, surface-enhanced Raman spectroscopy (SERS) has proved its effectiveness in terms of unswerving, extreme sensitivity as well as high selectivity for identification of analytes under examination [9] , [10] . The technique has progressively evolved from the basic detection of chemical finger-print of organic molecules towards an alternative bio-analytical tool for the detection of microbes to a greater extent with excellent specificity and reproducibility by tailoring the design of substrates [11] , [12] , [13] . Rapid trace level detection of micro-biological organisms with SERS will ease the spread of their diverse effects on human civilization.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon nanowires (Si NWs ) have gained interest in the last few years due to their versatility and properties like absorption, light emission, catalytic activity, and a wide range of applications. Among all its applications, they can be exploited for photocatalysis, [7][8][9][10] solar water splitting, 11,12 detection of molecules, [13][14][15] light trapping, 16,17 reduction of metals, 18 storage and energy conversion, 19 CO 2 reduction, 20,21 hydrogen generation, 22 and many other applications. Moreover, it has been reported that the decoration of silicon nanowires with metallic nanoparticles can enhance their catalytic properties, especially for electron discharging.…”
Section: Introductionmentioning
confidence: 99%
“…The Raman intensity decreases with decreasing the concentration of R6G from 10 À 6 to 10 À 12 m, and it can clearly identify the main characteristic peaks until the concentration of 10 À 12 m, implying the LOD of R6G on GO-g-PSSA/Ag film is as low as 10 À 11 m. Some of the recently reported Ag-based SERS substrates have same or much higher LOD values compared to our work. [42][43][44] Although, much lesser LOD values (10 À 13 m and 10 À 16 m) are also reported, those works involve some complex synthesis or treatments. [45,46] The plot of Raman intensity of the peak at 613 cm À 1 recorded from GO-g-PSSA/Ag film versus logarithmic concentration of R6G is shown in Figure 6B.…”
Section: Chemistryselectmentioning
confidence: 99%